Environmental upgrading in global value chains: The potential and limitations of ports in the greening of maritime transport. Issue 89 (February 2018) - Poulsen, René Taudal; Ponte, Stefano; Sornn-Friese, Henrik
Highlights: We examine ports' potential for greening maritime transport and global value chains. Ports hold considerable potential for facilitating environmental upgrading. High visibility of emissions is key for upgrading and should be further enhanced. High tool implementation complexity can be tackled by enhanced collaboration. Ports should forge alliances with cargo-owners to green maritime transport. Abstract: Ports are crucial hubs in the functioning of the global economy, and maritime transport is a major emitter of air pollutants. Ports have considerable potential for promoting environmental upgrading in maritime transport and along global value chains more generally, but so far have been only partially successful in doing so. We examine results, limitations and future potential of voluntary initiatives that have been carried out by selected European and North American port authorities, which are considered frontrunners in environmental management. Drawing from the insights of global value chain analysis and organizational theory, we find that low 'tool implementation complexity' and high 'issue visibility' concerning emissions are key facilitators of environmental upgrading. We suggest that ports can intervene in two main ways to improve the environmental performance of maritime transport beyond their organizational and physical boundaries: by lowering tool implementation complexity through stronger collaboration within global value chains; and by enhancing emission visibility through alliances with cargo-owners and regulators.